PENGARUH TAX AVOIDANCE, UKURAN PERUSAHAAN, DEBT EQUITY RATIO, DAN UMUR PERUSAHAAN TERHADAP BIAYA UTANG PADA PERUSAHAAN MANUFAKTUR - Gresya, Hanny; Arofah, Anastasia Anggarkusuma; Khusnia, Aulia Nisa (UNPERBA, 2024)
Tax Avoidance is an activity to minimize tax financing by companies. Although legally this activity is legal, this is contrary to the government's efforts to increase state tax revenues. One of the tax avoidance practices that can be carried out by companies is to conduct external financing through debt costs. The cost of debt is the rate of return arising from the company's debt transactions to external parties. Factors that are suspected of influencing the cost of debt other than tax avoidance include company size, debt equity ratio, and company age. This research tries to explore the relationship between these factors and the cost of debt in manufacturing companies in the food and beverage sector in 2018–2021. Data from this study used secondary data obtained from the Indonesia Stock Exchange for the period 2018 – 2021. The total sample used in this study was 60 samples. Sampling using purposive sampling technique. Data analysis used multiple linear regression analysis using the SPSS 23 program. The results showed that the variables Tax Avoidance, Company Size and Debt to Equity Ratio had no effect on debt costs, while company age had a positive and significant effect on Cost of Debt in listed manufacturing companies on the Indonesian Stock Exchange.